2021
DOI: 10.1038/s41598-021-98130-5
|View full text |Cite
|
Sign up to set email alerts
|

Strong tribo-piezoelectric effect in bilayer indium nitride (InN)

Abstract: The high electronegativity between the atoms of two-dimensional (2D) group-III nitrides makes them attractive to demonstrating a strong out-of-plane piezo-electricity effect. Energy harvesting devices can be predicted by cultivating such salient piezoelectric features. This work explores the tribo-piezoelectric properties of 2D-indium nitride (InN) as a promising candidate in nanogenerator applications by means of first-principles calculations. In-plane interlayer sliding between two InN monolayers leads to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…The epitaxial growth of single-crystal graphene on a macrosized (up to 0.5 m) single-crystal Cu(111) foil has recently been achieved, opening the door for the epitaxial growth of single crystals of other promising two-dimensional (2D) materials. In particular, significant effort has been given to achieving the growth of wafer scale 2D hexagonal boron nitride ( h -BN) because of its outstanding electrical, mechanical, , thermal, optical, and chemical properties. Although top-down processes such as mechanical or watery exfoliation make it easy to produce high-grade h -BN, the exfoliated flake size is small and the thickness varies greatly, restricting the development of practical applications. The bottom-up strategy such as chemical vapor deposition (CVD) is the most favorable approach owing to its mass fabrication capability and variable controllability through the growth phase.…”
Section: Introductionmentioning
confidence: 99%
“…The epitaxial growth of single-crystal graphene on a macrosized (up to 0.5 m) single-crystal Cu(111) foil has recently been achieved, opening the door for the epitaxial growth of single crystals of other promising two-dimensional (2D) materials. In particular, significant effort has been given to achieving the growth of wafer scale 2D hexagonal boron nitride ( h -BN) because of its outstanding electrical, mechanical, , thermal, optical, and chemical properties. Although top-down processes such as mechanical or watery exfoliation make it easy to produce high-grade h -BN, the exfoliated flake size is small and the thickness varies greatly, restricting the development of practical applications. The bottom-up strategy such as chemical vapor deposition (CVD) is the most favorable approach owing to its mass fabrication capability and variable controllability through the growth phase.…”
Section: Introductionmentioning
confidence: 99%
“… 13 16 Moreover, employing a surface-confined nitridation technique, micrometer-sized 2D-GaN has been synthesized recently. 17 , 18 InN-based nanostructures 19 , 20 are also improving day by day. Therefore, the application prospects of monolayer XN in the field of NEMS such as nanoenergy harvesting, energy storage, sensing, and piezotronics are exciting, and the investigation of the mechanical properties at different circumstances attracts great attention.…”
Section: Introductionmentioning
confidence: 99%
“… 36 − 42 Moreover, a van der Waals heterobilayer built by XN has also been explored recently. 20 From these studies, it has been found that monolayer XN is very much promising and can be successfully employed in different piezoelectric, optoelectronic, photocatalytic, and sensing applications. Although most of the existing works has focused on studying the structural, electronic, and optical properties of XN, to the greatest of our understanding no studies have reported on the tensile mechanical behavior of this prospective monolayer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations